A Dual-Robot Welding Path Planning Method Based on Kmeans and Ant Colony Algorithms - Wang, Jingjing; Deng, Hongli; Wang, Cun; Cao, Xinliang (Proceedings (International Conference on Informative and Cybernetics for Computational Social Systems. Online), 2021)
For the problem of double robots working together in the welding process, this project proposes a path planning method based on Kmeans algorithm and ant colony algorithm. The Kmeans algorithm is used to classify all weld joint tasks and reasonably assign them to individual robots. The ant colony algorithm is used to sort the weld joints assigned to individual robots and also to plan the work route for each robot. The simulation results show that the task assignment to this method is more scientific and reasonable than the existing methods, and the path planning results are shorter than the existing ones.